2001
DOI: 10.1002/1097-4652(200102)186:2<169::aid-jcp1023>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Cervical cancer vaccines: Emerging concepts and developments

Abstract: Certain human cancers are linked to infection by oncogenic viruses that are able to cause transformation of the normal host cell into a cancerous cell. Human papillomavirus (HPV) DNA and expression of viral transforming proteins are found in virtually all cervical cancer cells, indicating an important role of this virus in the pathogenesis of the disease. Evidence exists that the immune response to cancer cells can play a major role in determining the outcome of disease. The fact that HPV is a necessary cause … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
31
0
4

Year Published

2001
2001
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(35 citation statements)
references
References 127 publications
(38 reference statements)
0
31
0
4
Order By: Relevance
“…Many prophylactic and therapeutic vaccine strategies are currently under development or in clinical trial. 3,4 The HPV16 oncoproteins E6 and E7, expressed in cervical carcinoma, are crucial for the development and the maintenance of the malignant phenotype. 1 These antigens are valuable targets for immunotherapy of tumors because they are able to elicit CTLmediated tumor rejection.…”
mentioning
confidence: 99%
“…Many prophylactic and therapeutic vaccine strategies are currently under development or in clinical trial. 3,4 The HPV16 oncoproteins E6 and E7, expressed in cervical carcinoma, are crucial for the development and the maintenance of the malignant phenotype. 1 These antigens are valuable targets for immunotherapy of tumors because they are able to elicit CTLmediated tumor rejection.…”
mentioning
confidence: 99%
“…O presente artigo de revisão explora os possíveis co-fatores do HPV na gênese do carcinoma escamoso do colo uterino, levando em conta apenas os fatores cuja associação com o vírus ou câncer cervical tenha sido documentada experimentalmente, e não apenas clínica ou epidemiologicamente. Dentre os 2,6,16,34,36,40,42,47,52,55 , bem como pelo esforço recente de pesquisadores no desenvolvimento de vacinas contra este vírus, com a finalidade de prevenção deste tipo de câncer 26,30,45,52 . A partir daí, esta revisão passa a explorar os possíveis co-fatores do HPV no processo de carcinogênese, levando em conta apenas os fatores cuja a associação com o vírus ou câncer cervical tenha sido documentada experimentalmente, e não apenas clínica ou epidemiologicamente.…”
unclassified
“…Viral antigens in tumors are known to be tumor specific antigens (eg HPV 16/18 E6 and E7 in cervical carcinoma) and serve as useful Leukemia targets for vaccination. 30 However, translocation products expressed in leukemia cells are also promising candidates as tumor antigens. Previous studies showed that leukemogenesisassociated fusion proteins, such as BCR/ABL 31,32 and PML/RAR␣, 33 have antigenicity and can act as leukemiaspecific antigens.…”
Section: Vaccination Against Tel/aml1 Positive Pre-b All Cellsmentioning
confidence: 99%